2020
DOI: 10.1590/s1980-220x2018058503571
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the use of physical restraint in intensive care patients

Abstract: Objective: To verify the frequency of physical restraint in patients and the factors associated with its use in the intensive care unit. Method: An observational and prospective study on the use of restraint in patients observed over two days, considering the variables: age and gender, personal and clinical characteristics, devices, adverse event and restraint use. The frequency was verified in three groups of patients with different conditions by applying the Chi-Squared, Likelihood Ratio or Kruskal-Wallis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Multivariate logistic regression analysis with the forward stepwise method was applied to our study based on a previous study with a similar sample size. 25 To minimalize independent variables, assessment tools with p values<0.05 in the initial univariate analysis were only included in the logistic model. The C-statistic was calculated to determine the accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate logistic regression analysis with the forward stepwise method was applied to our study based on a previous study with a similar sample size. 25 To minimalize independent variables, assessment tools with p values<0.05 in the initial univariate analysis were only included in the logistic model. The C-statistic was calculated to determine the accuracy of the model.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not consistent with previous studies that reported the main type was a full-enclosure bed rail to prevent falls in acute wards. 19,25 This difference may be explained by the disease stage. For example, while falls in acute care wards were mainly caused by rollover from a bed, 19 falls in sub-acute care wards tend to happen when transferring from a bed to other life spaces.…”
Section: Discussionmentioning
confidence: 99%
“…Çalışmaya katılan hemşirelerin, %45.4'ünün 26-30 yaş grubu arasında olduğu, %74.1'inin kadın; %64.8'inin bekar; %54.6'sının gelirinin gidere eşit; %79.6'sının çocuğunun olmadığı; %63'ünün lisans mezunu olduğu; %79.6'sının koroner yoğun bakımda çalıştığı; %59.3'ünün meslekte 1-5 yıl arasında çalıştığı; %50.9'unun haftalık 50 saat ve üzeri çalıştığı; %62'sinin bir günde 3-4 hasta baktığı; %78.7'sinin hasta merkezli çalıştığı; %40.7'sinin işinden memnun olmadığı bulunmuştur (Tablo 1). 12,13 . Özdelikara ve Kaya (2018); kısıtlamanın uygun şekilde yapıldığında ve bazı protokollere uyulduğunda hastanın iyileşme sürecine fayda sağlayacak bir uygulama olduğunu ve kısıtlama uygulayacak olan hemşirelerin kısıtlama dönemini iyi yönetmeleri için yasal yükümlülüklerinin bilincinde olmaları gerektiğini savunmuştur 7 .…”
Section: Bulgularunclassified
“…Kahraman ve Erden (2016)'in yapmış olduğu çalışmada ise; stres, deliryum, ajitasyon gibi faktörlerin ve hatta buna bağlı olarak gelişen planlanmamış ekstübasyonun hastaların hastanede yatış süresini uzatan ve tedavi sürecini engelleyen durumlar olduğu, bunların yetersiz fiziksel ve kimyasal tespitten kaynaklandığı belirtilmiştir 11 . Literatür incelendiğinde yapılan çalışmalarda, bakım ve tedavinin sürdürülmesi, hasta konforunun ve güvenliğinin sağlanması gibi amaçlarla kullanılan tespit uygulamaları, kullanılan materyallerin uygunsuz kullanılması, doğru teknik kullanılmaması ya da prosedürlere uyulmaması gibi sebeplerle yoğun bakım hastalarında olumsuz sonuçlara sebep olabilmektedir 12,13 . Bazı durumlarda hayat kurtarıcı olabilen ve hastanın güvenliği için kullanılması gereken tespit uygulamalarının, kullanılması gereken durumları, kontrendikasyonları ve komplikasyonları bilinerek yalnızca mecburi durumlarda kullanılması için politikalar geliştirilmeli ve personele eğitim verilmelidir 14 .…”
Section: Introductionunclassified